Synthesis and deposition of Silver nanostructures on the silica microsphere by laser-assisted photochemical method for SERS applications - Pham, Thanh Binh; Nguyen, Thuy Van; Cam Hoang, Thi Hong; Bui, Huy; Pham, Thanh Son; Nguyen, Van Phu; Pham, Hoi Van (Photonics Letters of Poland, 2020)
The homogeneous distribution of nano-metallic structures on the surface-enhanced Raman (SERS) substrates plays an important factor for high-sensitive Raman scattering measurement. In this paper, we present a low-cost laser-assisted photochemical method for making a SERS probe based on silver nanostructures, which are one-timely synthesized nano-silver structures, homogeneously deposited on silica microsphere surfaces. Achieved SERS-activity substrates with a homogeneous distribution of Ag-nanostructures are verified by a mapping technique on the surface of Ag-coated microsphere for the detection of low concentration of Rhodamine 6G in aqueous solutions in a range of 10-4-10-9M. The obtained results show that a SERS microsphere probe has a good repetition of SERS-activity in any space of sensing area, and large potential for application in a biochemical sensing technique. Full Text: PDF References Y. Chen et al., "Interfacial reactions in lithium batteries", J. Phys. D: Appl. Phys. 50, 02510 (2017). CrossRef T.B. Pham, H. Bui, H.T. Le, V.H. Pham, "Characteristics of the Fiber Laser Sensor System Based on Etched-Bragg Grating Sensing Probe for Determination of the Low Nitrate Concentration in Water", Sensors 17, 0007 (2017). CrossRef X. Wang, O.S. Wolfbeis, "Fiber-Optic Chemical Sensors and Biosensors (2013–2015)", Anal. Chem. 88, 203 (2016). CrossRef R. Wang, K. Kim, N. Choi, X. Wang, J. Lee, J.H. Joen, G. Rhie, J. Choo, "Highly sensitive detection of high-risk bacterial pathogens using SERS-based lateral flow assay strips", Sens. Actuators B-Chem. 270, 72 (2018). CrossRef H. Zhang et al., "Determination of Pesticides by Surface-Enhanced Raman Spectroscopy on Gold-Nanoparticle-Modified Polymethacrylate", Anal. Let. 49, 2268 (2016). CrossRef L. Chen, H. Yan, X. Xue, D. Jiang, Y. Cai, D. Liang, Y.M. Jung, X.X. Han, B. Zhao, "Surface-Enhanced Raman Scattering (SERS) Active Gold Nanoparticles Decorated on a Porous Polymer Filter", Appl. Spectrosc. 71, 1543 (2017). CrossRef A. Matikainen, T. Nuutinen, P. Vahimaa, S. Honkanen, "A solution to the fabrication and tarnishing problems of surface-enhanced Raman spectroscopy (SERS) fiber probes", Sci. Rep. 5, 8320 (2015). CrossRef J. Zhang, S. Chen, T. Gong, X. Zhang, Y. Zhu, "Tapered Fiber Probe Modified by Ag Nanoparticles for SERS Detection", Plasm. 11, 743 (2016). CrossRef W. Xu et al., "A Dual-Butterfly Structure Gyroscope", Sensors 17, 467 (2017). CrossRef K. Setoura, S. Ito, M. Yamada, H. Yamauchi, H. Miyasaka, "Fabrication of silver nanoparticles from silver salt aqueous solution at water-glass interface by visible CW laser irradiation without reducing reagents", J. Photochem. Photobio. A: Chem. 344, 168 (2017). CrossRef K. Liu, Y. Bai, L. Zhang, Z. Yang, Q. Fan, H. Zheng, Y. Yin, C. Gao, "Porous Au–Ag Nanospheres with High-Density and Highly Accessible Hotspots for SERS Analysis", Nano Lett. 16, 3675 (2016). CrossRef Z. Huang, X. Lei, Y. Liu, Z. Wang, X. Wang, Z. Wang, Q. Mao, G. Meng, "Tapered Optical Fiber Probe Assembled with Plasmonic Nanostructures for Surface-Enhanced Raman Scattering Application", ACS Appl. Mater. Interfaces 7, 17247 (2015). CrossRef